2017
DOI: 10.1007/s10555-017-9684-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer complexity: implications of intratumoral heterogeneity in clinical management

Abstract: Generation of intratumoral phenotypic and genetic heterogeneity has been attributed to clonal evolution and cancer stem cells that together give rise to a tumor with complex ecosystems. Each ecosystem contains various tumor cell subpopulations and stromal entities, which depending upon their composition can influence survival, therapy responses and global growth of the tumor. Despite recent advances in breast cancer management, the disease has not been completely eradicated as tumors recur despite initial resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 72 publications
0
52
0
Order By: Relevance
“…Recently, cancer stem cells (CSCs) have been considered to be a source for initiation, invasion, metastasis and recurrence of breast tumour [39,40]. It has become a new strategy to simultaneously target the CSCs and the differentiated tumour cells by concomitant delivery of CSCs-targeting agents and traditional chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cancer stem cells (CSCs) have been considered to be a source for initiation, invasion, metastasis and recurrence of breast tumour [39,40]. It has become a new strategy to simultaneously target the CSCs and the differentiated tumour cells by concomitant delivery of CSCs-targeting agents and traditional chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, tumor hypoxia has been recognized as an important driver of intratumoral heterogeneity which in turn leads to the development of cell clones with an aggressive and treatment-resistant phenotype characterized by rapid progression, treatment failures, and patient deaths [1,2,[6][7][8][9]. Prior studies that investigated tumor hypoxia in breast cancer using the PET/CT imaging with the radiotracer [ 18 F]fluoromisonidazole ([ 18 F]FMISO) have shown that higher [ 18 F]FMISO-tumor-to-background-ratio (TBR) and estrogen receptor negativity were independent predictors of shorter disease-free survival, where higher [ 18 F]FMISO-TBR was associated with higher plasma levels of angiogenic hypoxic markers [55].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is a complex disease with remarkable intratumoral heterogeneity which leads to varied genetic, phenotypic, and behavioral characteristics; clinical presentations; and treatment responses [1][2][3][4][5][6]. Tumor hypoxia has been recognized as an important feature and a key driver of BC heterogeneity [7] that leads to the development of cell clones and an aggressive and treatment-resistant phenotype characterized by rapid progression and poor prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is the antithesis of molecular‐targeted therapy, the targets of which are the components of complex intracellular interactomes (Figure ). As in any complex system, phenotypic effects of molecular targeting in this case are unpredictable. Immune checkpoint therapy is a striking example of the success of the afore‐mentioned concept, but its complexity is manifested here by its rather high toxicity, and the enormous variability of patients’ responses—ranging from none to complete remission which presents an important problem …”
Section: Brief Summary Of Immune Checkpointsmentioning
confidence: 99%